Using Games to Learn English for Young Learners in Darussalam Elementary school - Desi Purnama Sari; Evi Lestaria (EDUJ : English Education Journal, 2023)
There are lots of schools in Indonesia still use conventional learning method in learning English. That is still using the book as a medium of learning. Learning English using games is still minimal and rarely uses technology as a learning medium. Using games can be used as an alternative learning media that can make the learning process more effective, engaging, and fun. This research aims to develop learning English by using games for young learners. The author uses a case study method to describe and analyze using games at a private school in Darussalam elementary school. The findings of this study are: (1) Students can improve their English skills by using games that have several values that are by student learning which make the game more suitable to be used as a medium for learning English in the classroom for students. With special needs; (2) There are some visible results through the game. First, learning styles suit students so that they feel interested in learning. Second, motivation and background affect each student's learning progress, especially in English.